Optimalisasi Sistem Informasi Akademik Berbasis Website dalam Mewujudkan Layanan Publik Berintegritas - Panji Suroso; Danny Ivanno Ritonga; Helsiana Sigalingging; Tri Danu Satria; Lanang Riyadi (SAP (Susunan Artikel Pendidikan), 2026)
Conventional academic services in higher education often face information fragmentation and limited document access, which hinder transparency. This study aims to analyze the optimization of a website-based academic information system in strengthening public service integrity at the Department of Sendratasik, Universitas Negeri Medan. A mixed-methods design was employed, combining quantitative surveys and qualitative interviews. A total of 186 active students at Universitas Negeri Medan participated in the survey to measure satisfaction levels before and after six months of system implementation in 2025/2026 , while 12 key informants were interviewed regarding governance challenges. The results showed that average student satisfaction increased significantly from 63% to 86% following the development of four departmental websites. The highest improvement occurred in digital document availability and academic information transparency. Qualitative findings revealed initial constraints involving limited infrastructure, varying digital literacy, and the absence of standardized digital procedures. Optimizing this system strengthens transparency, accountability, and digital documentation. The study concludes that website-based academic information systems serve as strategic instruments for digital integrity governance to enhance student satisfaction in higher education. It recommends strengthening digital policies, system integration, and continuous human resource development